1980
DOI: 10.1099/00221287-118-1-95
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron Microscopic Study of the Location of Group-Specific and Protein Type-Specific Antigens of Group B Streptococci

Abstract: 95The ultrastructural location of the group-specific polysaccharide and the type-specific protein antigens R and X of group B streptococci was studied by means of the direct immunoferritin technique. The group-specific antigen was located on the outer wall layer. The specificity of the reaction was proved by the inhibition of labelling after absorption of the antibody-ferritin conjugate with group B polysaccharide. On the other hand, the demonstration of the polysaccharide was not sterically hindered by protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Wild-type (WT) and isogenic mutant bacteria were stained with: i) mouse mAb S9 followed by 5 nm gold-labeled IgG; ii) with rabbit pAb anti-PilB followed by 10 nm gold-labeled IgG, and iii) with rabbit pAb anti PilA followed by 20 nm gold-labeled IgG. The mAb S9 decorates the external layer of the capsule [36] and its thickness in strain NEM316 was estimated to be ≈50 nm on ultra-thin sections by transmission electron microscopy (Figure S1). In the absence of the PilB backbone pilin, the PilA adhesin is found at the cell surface without detectable pili (Figure 3A, bottom panel).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type (WT) and isogenic mutant bacteria were stained with: i) mouse mAb S9 followed by 5 nm gold-labeled IgG; ii) with rabbit pAb anti-PilB followed by 10 nm gold-labeled IgG, and iii) with rabbit pAb anti PilA followed by 20 nm gold-labeled IgG. The mAb S9 decorates the external layer of the capsule [36] and its thickness in strain NEM316 was estimated to be ≈50 nm on ultra-thin sections by transmission electron microscopy (Figure S1). In the absence of the PilB backbone pilin, the PilA adhesin is found at the cell surface without detectable pili (Figure 3A, bottom panel).…”
Section: Resultsmentioning
confidence: 99%
“…Electron microscopy studies exposed the mosaictype appearance of the external bacterial surface (18). Type-specific capsular polysaccharides mask the group B binding sites, rendering the antigen inaccessible for binding unless the polysaccharide is removed or chemically altered (19).…”
Section: The Pathogenmentioning
confidence: 99%
“…All labelling experiments were done using the direct immunoferritin tech- nique. Conjugation of the IgG-fractions of type-and group-specific antisera with ferritin, incubation of walls with the conjugates, and the preparation of the samples for electron microscopy were carried out as previously described (Wagner et a/.. 1980).…”
Section: Bacterial Strains and Growth Conditions The Following Straimentioning
confidence: 99%
“…Using the immunoferritin technique, we have previously shown that the group-specific polysaccharide of group B streptococci (Streptococcus agalactiae) strains 24/60 (type X) and 25/60 (type R) is located on both the outer and inner surfaces of isolated walls whereas the protein antigens R and X are found only on the outer side (Wagner et al, 1980). Recently, Kasper & Baker (1979) used the same technique to demonstrate the type Ia, I1 and I11 polysaccharide antigens of group B streptococci.…”
Section: Introductionmentioning
confidence: 99%